2021
DOI: 10.1016/j.xcrm.2021.100252
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 protein subunit vaccination of mice and rhesus macaques elicits potent and durable neutralizing antibody responses

Abstract: The outbreak and spread of SARS-CoV-2 (severe acute respiratory syndrome-coronavirus-2) is a current global health emergency, and effective prophylactic vaccines are needed urgently. The spike glycoprotein of SARS-CoV-2 mediates entry into host cells, and thus is the target of neutralizing antibodies. Here, we show that adjuvanted protein immunization with soluble SARS-CoV-2 spike trimers, stabilized in prefusion conformation, results in potent antibody responses in mice and rhesus macaques, with neutralizing … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
32
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 66 publications
6
32
1
Order By: Relevance
“…We have demonstrated that two doses of a subunit vaccine consisting of a prefusion S trimer (Wuhan-Hu-1) formulated with liquid or lyophilized CoVaccine HT™ reduces viral load and provides sufficient, durable, cross-variant protection from mild to moderate disease lasting at least 3 months after the final boost. This supports previous findings in rhesus macaques that S trimer-based subunit protein vaccines are highly immunogenic and generate long-lasting, robust antibody responses ( 68 ). Furthermore, using a two-step purification method of immunoaffinity chromatography followed by a size-exclusion polishing step results in a homogenous antigen composition and reduces host-cell carryover plaguing conventional purification strategies for protein subunits ( 69 ).…”
Section: Discussionsupporting
confidence: 92%
“…We have demonstrated that two doses of a subunit vaccine consisting of a prefusion S trimer (Wuhan-Hu-1) formulated with liquid or lyophilized CoVaccine HT™ reduces viral load and provides sufficient, durable, cross-variant protection from mild to moderate disease lasting at least 3 months after the final boost. This supports previous findings in rhesus macaques that S trimer-based subunit protein vaccines are highly immunogenic and generate long-lasting, robust antibody responses ( 68 ). Furthermore, using a two-step purification method of immunoaffinity chromatography followed by a size-exclusion polishing step results in a homogenous antigen composition and reduces host-cell carryover plaguing conventional purification strategies for protein subunits ( 69 ).…”
Section: Discussionsupporting
confidence: 92%
“…There are many types of COVID-19 vaccines currently available for prophylaxis, and many are under development ( Mandolesi et al, 2021 ). Several therapeutics are available based on WHO guidelines to treat the complications of COVID-19 and related complications ( Lamontagne et al, 2021 ); however, these therapeutics are not specifically designed for the treatment of COVID-19 and its related complications such as Neuro-COVID, and their efficacies substantially differ across the globe and are not very effective in ameliorating disease severity ( Surnar et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Employing the classical subunit approach, S subunit vaccine candidates have generated different levels of neutralizing antibody responses in preclinical testing (Liang et al, 2021;Liu et al, 2020b;Mandolesi et al, 2021;Tan et al, 2021a;Zang et al, 2020). Employing self-assembly strategies of S or RBD further increased immune responses (Walls et al, 2020a;Zhang et al, 2020a) and protected against infection (Arunachalam et al, 2021;Brouwer et al, 2021;Guebre-Xabier et al, 2020).…”
Section: Introductionmentioning
confidence: 99%